HAMKA'S AND ZA'ABA'S EDUCATIONAL INSIGHTS: A COMPARATIVE STUDY - Yuslan, Siti Nursyakirah; Bin Zamziba, Muhammad Nur Farhan; Yusuf, Imtiyaz (Abjadia : International Journal of Education, 2024)
This research paper examines the educational thoughts of two prominent Malay-Muslim scholars, Za'ba (Zainal Abidin Ahmad) (d. 1973) and Hamka (Haji Abdul Malik Karim Amrullah) (d. 1981), in the context of their contributions to education and society. Despite sharing a common era, Za'ba and Hamka had distinct views on education, influenced by their beliefs in the synthesis of modern knowledge and Islamic values. Therefore, this paper seeks to explore the similarities and differences in their concept of education. The authors implemented library research with content analysis and comparative studies based on the works of the aforementioned scholars. Hamka’s concept of education is based on his selected works namely Falsafah Hidup, Lembaga Budi and Lembaga Hidup. While for Za’ba, his thoughts are studied based on his work Jalan Keselamatan bagi Orang-Orang Melayu, Kemiskinan Melayu and other related writings of the discourse on Za’ba’s thought. The concept of education according to Hamka and Za’ba puts a strong emphasis on the significance of comprehensive knowledge that combines the perfection of intellectual, physical, and spiritual aspects of a man. Hamka’s emphasis of education is on shaping characters to produce a man who is capable of contributing to society. While Za’ba emphasis on education for the Malays. This paper delves into their perspectives, emphasizing their stances on the integration of Western education and Islamic teachings, their views on effective teaching and learning methods, important elements in education, and their approaches to curriculum development.